2021
DOI: 10.3390/su13095138
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supply Chain Management Strategy on Operational and Financial Performance

Abstract: Given that small and medium manufacturing enterprises (SMEs) are key to national economic development, the application of supply chain strategies that support their sustainability is critical. This study aims to identify the effects of supply chain management (SCM) on the operational performance of SMEs in Korea, specifically considering organizational competencies. To achieve this, an empirical survey was conducted on 300 Korean manufacturing SMEs that had introduced SCM strategies. The relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 58 publications
0
11
0
3
Order By: Relevance
“…This finding is corroborated with the findings of Lee (2021) whereby automotive companies in Malaysia should prioritise their resources in addressing the Strategic Barrier (C1). Lee (2021) declares that strategies of SCM have major impacts on organisations including the automotive industry. Addressing the Strategic Barrier (C1) enables the Malaysian automotive industry to create a clear vision and direction for the organisation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is corroborated with the findings of Lee (2021) whereby automotive companies in Malaysia should prioritise their resources in addressing the Strategic Barrier (C1). Lee (2021) declares that strategies of SCM have major impacts on organisations including the automotive industry. Addressing the Strategic Barrier (C1) enables the Malaysian automotive industry to create a clear vision and direction for the organisation.…”
Section: Discussionmentioning
confidence: 99%
“…Successful business operations require high-level process integration. Supply chain efficiency can only be improved if all parties and activities are linked together (Lee, 2021). An increase in integration might substantially impact costs, quality, variety, and service (Joghee et al, 2021;Karimi & Rafiee, 2014).…”
Section: Relationship and Impact Of Supply Chain 40 On Organizational...mentioning
confidence: 99%
“…According to Abbasi et al (2021) and Ryu et al 2016), supply chain strategy is positively correlated with supply chain management commitment. According to Lee (2021), supply chain strategy improves supply chain management and capabilities in logistics, this could result in improved business performance. Supply chain strategy, according to (Dubey et al, 2018a;Patel, 2017), rules both things at the same time (regulation of universality and integration in the business of doing business).…”
Section: Supply Chain Strategymentioning
confidence: 99%
“…According to Kalaitzi et al (2018), inter-company supply chain methods have been demonstrated to be efficient in attaining common goals across all departments, from procurement to production, distributors, retail, and consumers (Lee, 2021). Organizations are beginning to recognize that increasing efficiency within a company alone will not be enough in today's dynamic global market environment; the entire supply chain must be competitive (Moradinasab et al, 2018).…”
Section: Introductionmentioning
confidence: 99%